2017
DOI: 10.4102/jir.v2i1.25
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxybutyrate improves β-cell mitochondrial function and survival

Abstract: Pharmacological interventions aimed at improving outcomes in type 2 diabetes and achieving normoglycaemia, including insulin therapy, are increasingly common, despite the potential for substantial side effects. Carbohydrate-restricted diets that result in increased ketogenesis have effectively been used to improve insulin resistance, a fundamental feature of type 2 diabetes. In addition, limited evidence suggests that states of ketogenesis may also improve β-cell function in type 2 diabetics. Considering how l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Recent study supported these results about anti-oxidant properties of βOHB 25). βOHB also improves mitochondrial function and increases ATP production in pancreatic beta cells and neuronal cells 26)27). In line with these findings, we found that βOHB increased intracellular ATP levels and restored mitochondrial dysfunction in cardiomyocytes (Figure 3E and F).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recent study supported these results about anti-oxidant properties of βOHB 25). βOHB also improves mitochondrial function and increases ATP production in pancreatic beta cells and neuronal cells 26)27). In line with these findings, we found that βOHB increased intracellular ATP levels and restored mitochondrial dysfunction in cardiomyocytes (Figure 3E and F).…”
Section: Discussionsupporting
confidence: 89%
“…Several studies support our findings about the cardioprotective role of βOHB. Ketone bodies are effective energy source of failing heart and increase survival in aging mice 26)28). Exogenous βOHB infusion protects ischemic injury in heart by reducing ROS and enhancing adenosine trisphosphate production 29).…”
Section: Discussionmentioning
confidence: 99%
“…Cells and tissue were prepared for mitochondrial respiration as described previously [ 35 , 36 , 37 , 38 ] before being transferred to respirometer chambers using the Oroboros O2K oxygraph (Oroboros, Innsbruck, Austria). Electron flow through complex I was supported by glutamate + malate (10 mM and 2 mM, respectively) to determine leak oxygen consumption (GM L ).…”
Section: Methodsmentioning
confidence: 99%
“…It may be the case that the down regulation of the rapid insulin release may not be wholly pathological if one considers it as a means to reduce any excess insulin signal on the liver to inhibit glycogenolysis. However, this is hypothetical and it is more likely that mitochondrial damage results in the pathological changes that impair the first phase rapid insulin response after a glucose bolus in T2DM patients, and this, in turn, contributes to a pathological feedforward progression of increases in fasting basal insulin levels [29,50,55,126].…”
Section: An Alternative Hypothesis: Insulin's Main Role Is To Regulate Beta-hydroxybutyrate Synthesismentioning
confidence: 99%